Spectral analysis of lamellae evolution and constraining effects aided by nano-carbons: A coupled experimental and simulation study. (28th September 2015) - Song, Kenan; Zhang, Yiying; Meng, Jiangsha; Minus, Marilyn L.
Abstract: The effects of filler concentration on processing-structure-property relationships in polymer composites with low nano-carbon (nC) loadings (<1 wt%) have been investigated. Fibrillar structure was observed under scanning electron microscopy (SEM), and confirmed quantitatively by X-ray measurements. A one-dimensional correlation function analysis of small-angle X-ray scattering (SAXS) data is used to track development for both the crystalline and amorphous regions in lamellae of the polymer matrix as a function of filler concentration and drawing temperature. Analysis for the filled poly(vinyl alcohol) (PVA) fibers demonstrates that the presence of the carbon nanochips (CNC) influences the organization and formation of lamellae stacking, leading to variations in composite fiber grain structure. An increase in grains per unit fibril volume and higher degree of chain orientation along the fiber axis was observed for the composites as compared to the control samples. Based on the fibrillar and lamellae dimensions of final stage fibers, mechanical simulations by finite element method (FEM) approaches were conducted on polymeric fibrils. Compared with molecular dynamics (MD) results, higher polymer constraining effects were related to increase of nano-particle inclusions. This work demonstrates the significance of using spectroscopy analysis and coupled simulation methods to provide detail information regarding the property–structure relationship in nano-composite fibers. Graphical abstract: Highlights: Structural evolutions have been observed and characterized using X-ray methods. PVA lamellae structure and grain size evolutions are determined by the one-dimensional correlation function. Nano-filler contraining effects were studied using experimentation, FEM, and MD.